Menghadapi Tantangan Modern: Katekese Kontekstual untuk Mahasiswa Calon Katekis - Maria Filisa Sopiah Sani; Intansakti Pius X (Sinar Kasih: Jurnal Pendidikan Agama dan Filsafat, 2024)
This research discusses the importance of developing effective contextual catechesis methods for prospective catechist students, especially in facing modern challenges involving social change, technology and contemporary moral issues. The focus of the research is to understand the integration of these aspects into religious teaching approaches to prepare students to apply religious values ​​in their daily lives. Spiritual challenges in the modern world, including clericalism and restrictions on the scope of catechists, require innovative and adaptive responses in learning and preaching approaches. This research uses a qualitative descriptive approach through literature study to investigate relevant literature. It is hoped that the results of this research will provide a theoretical and practical basis for religious educators, enabling prospective catechist students to integrate religious teachings with the context of their lives. Thus, this research contributes to developing catechesis methods that are responsive to changing times, preparing the younger generation to face spiritual challenges wisely in the ever-changing modern era.